Synopsis: Ethiopia's spatial and structural transformation: Public policy and drivers of change - Schmidt, Emily; Dorosh, Paul A.; Kedir Jemal, Mekamu; Smart, Jenny (International Food Policy Research Institute, 2019)
This research note evaluates Ethiopia’s demographic shift over the last four decades while also evaluating potential urbanization trends 20 years into the future.1 Propelling Ethiopia’s urban growth is new secondary city development, ongoing population growth in small towns, and improved access to markets. In order to understand how secondary city growth is contributing to urbanization, we update the agglomeration index for the country. In addition, we look at recent patterns of domestic migration. Reviewing the government’s investment strategy in industrial parks and sugar factories, we explore current plans for industrial zones in Ethiopia. In examining the scope for their success, we consider the key role that government policy will need to play in terms of overall investment in infrastructure, as well as the major implications of macro-economic and trade policies to motivate increased private sector investment in Ethiopia’s industrial sector.